Investigation of benzene-DNA adducts and their detection in human bone marrow. - Bodell, W J (1993)
We have examined DNA adduct formation in HL-60 cells and human bone marrow treated with either hydroquinone or p-benzoquinone and have found that these treatments produce the same DNA adduct in both cell types. The DNA adduct level from these treatments varied from 0.05 to 7.5 adducts per 10(7) nucleotides as a function of treatment time and concentration for both compounds. Reaction of calf thymus DNA with p-benzoquinone produced three adducts as detected by 32P-postlabeling. These adducts have been identified as (3'-hydroxy)-3,N4-benzetheno-2'-deoxycytidine-3'-phosphate; (3'-hydroxy)-1,N6-benzetheno-2'-deoxyadenosine-3'-phosphate; and (3'-hydroxy)-1,N2-benzetheno-2'-deoxyguanosine-3'-phosphate. The DNA adduct formed in HL-60 cells did not correspond to any of the principal adducts formed in DNA reacted with p-benzoquinone, suggesting that cellular environment modifies DNA adduct production by p-benzoquinone. These studies demonstrate that DNA adduct formation occurs in human bone marrow treated with benzene metabolites and suggest that P1-enhanced 32P-postlabeling may be used to detect DNA adducts resulting from benzene exposure.